2018
DOI: 10.1101/491902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Alzheimer risk genes determine the microglia response to amyloid-β but not to TAU pathology

Abstract: Background: Thousands of SNPs associated with risk of Alzheimer's disease (AD) in genome-wide association studies (GWAS) do not reach genome-wide significance. When combined, they contribute however to a highly predictive polygenic risk score. The relevance of these subthreshold risk genes to disease, and how their combined predictive power translates into functionally relevant disease pathways, is unknown. We investigate here at the genome-wide level and in an unbiased way to what extent AD risk genes show al… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
77
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 45 publications
10
77
0
1
Order By: Relevance
“…Consistent with this, we observed that AD risk genes that we identified here were enriched for a microglial co-expression module upregulated in AD postmortem brains (T-M3, Figure 4g) 39 . This module is different from the module associated with epigenetic dysregulation in AD (Figure 3g), suggesting that genetic risk factors and epigenetic regulation underscore different expression signatures in AD with distinct cellular specificities and likely causal relationships [49][50][51] .…”
Section: Genetic Risk Factors Associated With Ad Converge Onto Microgmentioning
confidence: 86%
“…Consistent with this, we observed that AD risk genes that we identified here were enriched for a microglial co-expression module upregulated in AD postmortem brains (T-M3, Figure 4g) 39 . This module is different from the module associated with epigenetic dysregulation in AD (Figure 3g), suggesting that genetic risk factors and epigenetic regulation underscore different expression signatures in AD with distinct cellular specificities and likely causal relationships [49][50][51] .…”
Section: Genetic Risk Factors Associated With Ad Converge Onto Microgmentioning
confidence: 86%
“…In addition, we found that, microglia 6 (cluster 8) was uniquely enriched in the IL-33 − tumors (Fig. 10c) and expressed genes involved in antigen presentation 106,108 (e.g., Cd74, H2-Aa, and H2-Ab1 (Supplementary Fig. 8a, b, g)).…”
Section: Plbd1mentioning
confidence: 88%
“…9a, b, d); (2) BMDM 4 (cluster 12), shows substantial expression of genes involved in interferon signaling, including Ifit2, Ifit3, and Irf7 (refs. 105,106,108 ; Fig. 10f and Supplementary Fig.…”
Section: Plbd1mentioning
confidence: 99%
“…GWAS studies show in fact that much of the risk of sporadic AD is associated with genes expressed in micro-and astroglia (Jansen et al, 2019). These genes are strongly up-or downregulated when exposed to amyloid deposition (Salih et al, 2018;Sala Frigerio et al, 2019;Sierksma et al, 2019). It is clear that we need more in depth study of the protective and harmful cellular reactions that occur in the course of AD.…”
Section: Introductionmentioning
confidence: 99%